Comparison of therapies in lumbar degenerative disc disease: a network meta-analysis of randomized controlled trials. (March 2018) - Zigler, Jack; Ferko, Nicole; Cameron, Chris; Patel, Leena
Aim: To compare the efficacy and safety of total disc replacement, lumbar fusion, and conservative care in the treatment of single-level lumbar degenerative disc disease (DDD).Materials & methods: A network meta-analysis was conducted to determine the relative impact of lumbar DDD therapies on Oswestry Disability Index (ODI) success, back pain score, patient satisfaction, employment status, and reoperation. Odds ratios or mean differences and 95% credible intervals were reported.Results: Six studies were included (1417 participants). Overall, the activL total disc replacement device had the most favorable results for ODI success, back pain, and patient satisfaction. Results for employment status and reoperation were similar across therapies.Conclusion: activL substantially improves ODI success, back pain, and patient satisfaction compared with other therapies for single-level lumbar DDD.